Best Practice Kepemimpinan Kepala Sekolah dalam Meningkatkan Nilai Akreditasi di SMPN 5 Airgegas Bangka Belitung - Odi Sukma; Enung Hasanah (Universitas Kristen Satya Wacana, 2021)
This study aims to determine the best practices of principal leadership in increasing the accreditation of SMP Negeri 5 Airgegas. This research is a case study research. As an instrument in this study, researchers were present in the field to collect data, process data and check the validity of the data obtained. Researchers also conducted interviews with the principal and several teachers also. Researchers make direct observation. Data collection procedures are direct observation, in-depth interviews, and documentation. Data analysis was performed by reducing data, organizing data, and summarizing data. The results showed: (1) In increasing school accreditation, the principal must have a plan or program that all teachers must implement following their duties and responsibilities. (2) school accreditation can be increased if there is the empowerment of teachers, administrative staffs, and students, mastery of the principal of each teacher's duties, administrative staff, and students, and maximum program evaluation. (3) The program must be published or socialized so that it is supported and implemented by teachers, administrative staffs and students according to their responsibilities. (4) the commitment of teachers and students, infrastructure is a supporting factor for the achievement of increasing school accreditation and the inhibiting factor to increase school accreditation is a lack of function and role.